The Experiential Theatre of Anthony Neilson and The Wonderful World of Dissocia - Ahmet Gökhan Biçer (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Experiential theatre goes beyond the boundaries of dramatic theatre by allowing the audience to experience the event performed on stage and create their own meaning and interpretation of conflicting phenomena, such as security and violence. As one of the important representatives of this type of English theatre in the 1990s, the playwright Anthony Neilson, has attracted substantial critical attention for his trenchant portrayal of violence in all its bareness that inevitably comes out within the practices of daily life. With one of his most important plays to date, The Wonderful World of Dissocia (2004), Neilson portrays experiential theatricality of states of mind while exploring the connection between the internal and external reality of a self. By doing so, Neilson pushes the framework of experiential theatre to a new extreme. This paper scrutinizes his contribution to the practice of experiential theatre within the context of violence and identity politics.